The Influence Of Social Proof, Brand Advocacy, Digital Campaigns And Digital Literacy Abilities On Instagram In Building Yotta's Purchase Intention - Andi Caezar To Tadampali; Ika Wisudawaty; Sri Hutami Adiningsih S (International Journal of Education, Vocational and Social Science, 2025)
Marketing in the digital era has evolved with the advent of social media-based marketing strategies. Social media-based marketing strategies are becoming increasingly important for both large companies and MSMEs in building purchase intention for their products. Yotta, a well-known beverage brand in Makassar, presents a digital campaign with the tagline #SemangatYo. The #SemangatYo digital campaign is a form of Yotta's initiative to increase consumer visibility and engagement through digital platforms. This study aims to analyze the influence of social proof, brand advocacy, digital campaigns, and digital literacy on Instagram in building purchase intention for Yotta. This study uses quantitative methods with techniquesnon probability samplingwith the type of sample taken in the research, namelypurposive sampling. This study was conducted through an online questionnaire with 97 respondents from Generation Y and Generation Z who had purchased Yotta products, followed Yotta's Instagram account, and resided in South Sulawesi. Data analysis techniques used classical assumption tests and multiple regression analysis to examine the influence of independent variables (social proof, brand advocacy, digital campaigns, digital literacy) on the dependent variable (purchase intention). The results of the study indicate that the four independent variables simultaneously have a positive and significant influence on Yotta's purchase intention among generation Y and generation Z in South Sulawesi. Partially, the social proof and brand advocacy variables on Yotta's Instagram do not have a positive and significant influence on Yotta's purchase intention among generation Y and generation Z in South Sulawesi. Meanwhile, the digital campaign and digital literacy variables on Yotta's Instagram partially have a positive and significant influence on Yotta's purchase intention among generation Y and generation Z in South Sulawesi. Then the coefficient of determination has a value of 81.5% which indicates that there is 81.5% of the influence of social proof, brand advocacy, digital campaigns, and digital literacy simultaneously on purchase intention while the remaining 18.5% is influenced by other variables that are not used as variables in this study.